The longest-lived spider: Mygalomorphs dig deep, and persevere - Mason, Leanda; Wardell-Johnson, Grant; Main, B. (Surrey Beatty and Sons, 2018)
© CSIRO. We report the longest-lived spider documented to date. A 43-year-old, female Gaius villosus Rainbow, 1914 (Mygalomorphae: Idiopidae) has recently died during a long-term population study. This study was initiated by Barbara York Main at North Bungulla Reserve near Tammin, south-Western Australia, in 1974. Annual monitoring of this species of burrowing, sedentary mygalomorph spider yielded not only this record-breaking discovery but also invaluable information for high-priority conservation taxa within a global biodiversity hotspot. We suggest that the life-styles of short-range endemics provide lessons for humanity and sustainable living in old stable landscapes.